20-Year outcome of TFCC repairs. Issue 3 (4th May 2018) - Moloney, Maria; Farnebo, Simon; Adolfsson, Lars
Abstract: The aims of this study were to investigate the functional result and rate of osteoarthritis 15–25 years after a TFCC-repair. Forty-seven patients completed the questionnaire Patient Rated Wrist Evaluation (PRWE), and 43 had new X-rays. Fifty-seven percent had a simultaneous arthroscopy. Sixteen patients had later additional surgery to the wrist, of these eight had a reoperation of the TFCC-injury due to recurrent instability. Radiographs showed that 17.5% had developed radiocarpal osteoarthritis and 34% osteoarthritis in the distal radioulnar joint. The median PRWE result was 22.5. Patients with radiocarpal osteoarthritis and patients who had additional surgery had significantly worse scores. Patients who had undergone arthroscopy significantly less often had developed radiocarpal osteoarthritis. The result is acceptable but not impressive and efforts should be made to diagnose these injuries early and also diagnose associated injuries, advisably by arthroscopy.